2019
DOI: 10.1177/0734016819833141
|View full text |Cite
|
Sign up to set email alerts
|

Saving Children, Damning Adults? An Examination of Public Support for Juvenile Rehabilitation and Adult Punishment

Abstract: Research shows that public preferences about justice system approaches to decreasing illegal behavior distinguish between adult and juvenile offending. We also know that fear of crime and perceived risk of victimization typically strengthen support for harsh punishments and reduce support for rehabilitation. What has yet to be demonstrated—and that we examine here—is whether there are youth-specific differences in the way that crime salience affects public support for punitive versus rehabilitative policies an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Although it is preferable that the question was entirely focused on the general population rather than youth, the main drawback is that our estimates of punitiveness may be overly conservative. As several studies have shown, attitudes toward juvenile offenders are generally more forgiving than attitudes toward adult offenders except for when the offending is violent, repetitive, or involves the use of firearms (Bishop 2000;Roberts 2004;Welch, Butler, and Gertz 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is preferable that the question was entirely focused on the general population rather than youth, the main drawback is that our estimates of punitiveness may be overly conservative. As several studies have shown, attitudes toward juvenile offenders are generally more forgiving than attitudes toward adult offenders except for when the offending is violent, repetitive, or involves the use of firearms (Bishop 2000;Roberts 2004;Welch, Butler, and Gertz 2019).…”
Section: Discussionmentioning
confidence: 99%